Thoracic Spinal Anesthesia in a Patient with Peritoneal Tuberculosis with Massive Ascites and Bilateral Pleural Effusion for Laparotomy - Dwi Lunarta Docterina Sutanti Siahaan; Jadeny Sinatra; Ronald T.H. Tambunan; Agus Prima (CoinReads Media Prima, 2026)
Peritoneal tuberculosis is an extrapulmonary form of tuberculosis with nonspecific clinical manifestations, such as ascites and abdominal pain, often leading to delayed diagnosis. In advanced conditions, massive ascites combined with bilateral pleural effusion may significantly impair respiratory function and increase perioperative risk. General anesthesia, commonly used for laparotomy, may further worsen pulmonary complications in such high-risk patients. We report a case of a 23-years-old female with peritoneal tuberculosis complicated by massive ascites and bilateral pleural effusion who underwent laparotomy under thoracic spinal anesthesia. The patient presented with abdominal distension, dyspnea, anemia, and hypoalbuminemia, indicating a compromised physiological status. Considering the risks associated with general anesthesia, thoracic spinal anesthesia was selected. The procedure was successfully performed with stable intraoperative hemodynamics and no significant respiratory complications. Thoracic spinal anesthesia is a feasible regional technique for abdominal surgery, offering better respiratory outcomes and recovery compared to general anesthesia. This case demonstrates its potential as a safe alternative in high-risk patients undergoing laparotomy.